Coupled exciton-trion spin dynamics in a MoSe2 monolayer. (3rd September 2018) - Anghel, S; Passmann, F; Ruppert, C; Bristow, A D; Betz, M
Abstract: Understanding and controlling the spin degree of freedom in two-dimensional transition metal dichalcogenides offers the potential for designing functional quantum materials. This work investigates the dynamics of photo- and resident carrier spins in an encapsulated MoSe2 monolayer using non-degenerate time-resolved Kerr-rotation microscopy. The lightly doped monolayer exhibits clear exciton and trion resonances with spin-polarizations that are characterized by a fast ( 20 ps) decay attributed to photocarrier relaxation and recombination, followed by a slow ( 690 ps) decay associated with resident carrier depolarization. Dual-frequency Kerr-rotation spectra directly reveal exciton-trion coupling on ultrashort timescales and within the spin coherence time of the system. Moreover, the distribution of the exciton-trion coupling features exposes inhomogeneous broadening likely arising from different domains within the excitation spot.